Protection of Space Environment in the Light of Perspective Challenges of “Space Wars” - Hurova, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
In article it is analyzed action in the space of the principle of prohibition of the use of force and threats (jus contra bellum). Also it is researched application of Geneva Law to space conflicts (jus in bello) and it correlations with another hard and soft norms of international law in the light of protection of space environment such as Convention on the Prohibition of Military or Any Other Hostile Use of Environmental Modification Techniques, Declaration of the United Nations Conference on the Human Environment 1972, Rio Declaration on Environment and Development 1992 etc. Beside this it is used practice of International Court of Justice for argumentation of positions and conclusions. Since space objects management is done remotely with help of software, author draw parallels between legal regulation of international conflicts in outer space and cyber space. Furthermore, it is researched specific features of application the principle of proportionality in international space armed conflicts with the aim of protection environment of space and Earth.